Keanekaragaman dan Kekerabatan Syzygium aksesi Purwokerto - Edy Purnomo Hadi; Yayu Widiawati; Sukarsa Sukarsa (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
A study on the diversity and phenetics of Syzygium in Purwokerto has been conducted. The aim of this study was to find out the diversity and phenetic relationship of Syzygium cultivars. The method used in this study is explorative survey, by recording all available cultivars. The data were analysed descriptively and the data were analysed with UPGMA. The result of this study showed that there were four spesies dan seven cultivars of Syzygium namely S. aqueum, S. samarangense including cultivar S. samarangense ‘Kaget Merah’, ‘Kaget Putih’, ‘Kaget Hijau’, ‘Madura Putih’, ‘Delima’, ‘Lilin Merah’, ‘Lilin Merah Jambu’, S. malaccense dan S. jambos. The results of phenetic analysis showed that there were four groups namely S. samarangense, A. aqueum, S. malaccense, and S. jambos.